Peer support for smoking cessation: a protocol of systematic review and meta-analysis - Hyun-Ju Seo (BMC, 2021)
Abstract Background Peer-support programs are a useful social support strategy for populations trying to quit smoking who are willing to maintain smoking abstinence. This study is a protocol for a systematic review and meta-analysis to assess the effectiveness of peer support for smoking cessation. Methods This protocol will be conducted in accordance with the Cochrane Handbook of Systematic Reviews of Interventions 6.2. We will conduct a comprehensive search in the Cochrane Central Register of Controlled Trials, ovidEmbase, PsycINFO, the Cumulative Index to Nursing and Allied Health Literature, ovidMEDLINE, Google Scholar, and Open Grey, as well as the Trials Register of Promoting Health Interventions in EPPI-Centre, ClinicalTrials.gov, the WHO International Clinical Trials Registry Platform, and reference lists of included papers. The review will include randomized controlled trials of peer support interventions aimed to stop smoking in any population. Two reviewers will independently screen and select relevant studies. Version 2 of the Cochrane tool that assesses risk of bias in randomized trials will be used to assess the risk of bias in the included studies. The primary outcomes will be defined as the tobacco abstinence rate and adverse events. If a quantitative synthesis is not appropriate, a synthesis without meta-analysis will be undertaken. Discussion This review will provide the best available evidence regarding the effects of peer support interventions to quit smoking. The results from this study will help to inform healthcare providers on the optimal peer support intervention modalities such as intensity, delivery methods, type of support provider, and duration of the intervention. Systematic review registration PROSPERO CRD42020196288